Effects of expanders (high shear conditioning) on growth performance in finishing pigs - Johnston, S.L.; Traylor, S.L.; Hines, Robert H.; Sorrell, S.P.; Kim, I.H.; Kennedy, G.A.; Hancock, Joe D.; Behnke, Keith C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Diets that had been processed using standard, long-term, and expander (high shear) conditioning tended to support greater ADG than an unconditioned meal control diet. Pelleting was necessary to maximize efficiency of growth, but only with standard and long-term conditioning. Indeed, the best efficiencies of gain were for pigs fed the expander processed diets, with no additional benefits from pelleting the expanded mash.
Keywords: Swine; Expander; Pellet; Ulcers; Finishing pigs